Gut microbiome of helminth-infected indigenous Malaysians is context dependent - Man, Zi Tee; Yi, Xian Er; Alice V., Easton; Nan, Jiun Yap; Li, Li Lee; Joseph, Devlin; Ze, Chen; Kee, Seong Ng; Pooranii, Subramanian; Angelina, Angelova; Oyebola, Oyesola; Shushan, Sargsian; et al. (BioMed Central, 2022)
Background: While microbiomes in industrialized societies are well characterized, indigenous populations with traditional lifestyles have microbiomes that are more akin to those of ancient humans. However, metagenomic data in these populations remains scarce, and the association with soil-transmitted helminth infection status is unclear. Here, we sequenced 650 metagenomes of indigenous Malaysians from fve villages with diferent prevalence of helminth infections. Results: Individuals from villages with higher prevalences of helminth infections have more unmapped reads and greater microbial diversity. Microbial community diversity and composition were most strongly associated with different villages and the efects of helminth infection status on the microbiome varies by village. Longitudinal changes in the microbiome in response to albendazole anthelmintic treatment were observed in both helminth infected and uninfected individuals. Inference of bacterial population replication rates from origin of replication analysis identifed specifc replicating taxa associated with helminth infection. Conclusions: Our results indicate that helminth efects on the microbiota were highly dependent on context, and efects of albendazole on the microbiota can be confounding for the interpretation of deworming studies. Furthermore, a substantial quantity of the microbiome remains unannotated, and this large dataset from an indigenous population associated with helminth infections is a valuable resource for future studies